2016
DOI: 10.1038/srep32728
|View full text |Cite
|
Sign up to set email alerts
|

Microwave ablation of hepatocellular carcinoma as first-line treatment: long term outcomes and prognostic factors in 221 patients

Abstract: This retrospective study aimed at evaluating the long-term outcomes and prognostic factors of microwave ablation (MWA) as a first-line treatment for hepatocellular carcinoma (HCC). 221 consecutive patients receiving MWA in our center between October 11, 2010 and December 31, 2013 were enrolled. Technique effectiveness was evaluated one month post-ablation. Initial complete ablation (CA1st) was gained in 201 (90.95%) patients, secondary CA (CA2nd) in 8 (3.62%) patients and the remaining 12 (5.43%) patients suff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 27 publications
3
22
0
Order By: Relevance
“…In addition, multiple nodules, large tumor size and high AFP level were risk factors for poor OS. This result suggested that the tumor characteristics play a key role in the prognosis of patients, which was consistent with previous studies [24,25]. At present, imaging technologies like CEUS, CT and MRI are most commonly used to evaluate the technical effectiveness of MWA [26].…”
Section: Discussionsupporting
confidence: 89%
“…In addition, multiple nodules, large tumor size and high AFP level were risk factors for poor OS. This result suggested that the tumor characteristics play a key role in the prognosis of patients, which was consistent with previous studies [24,25]. At present, imaging technologies like CEUS, CT and MRI are most commonly used to evaluate the technical effectiveness of MWA [26].…”
Section: Discussionsupporting
confidence: 89%
“…With the aid of 3D US-CEUS fusion imaging, 33.7% (30/89) of the lesions estimated as Grade B received supplementary ablation, thus reducing the proportion of Grade B lesions to 7.9% (7/89). Finally, the technique effectiveness rate was 98.8% (81/82), higher than the range of 67.7-93.5% reported in previous studies under guidance by conventional US [22][23][24][25][26][27] and identical to the rate reported by Park et al (100%), who evaluated the usefulness of 3D US-US fusion imaging for the guidance of RFA of HCC [28]. In addition, no major complications occurred in these patients.…”
Section: Discussionsupporting
confidence: 62%
“…Hepatocellular carcinoma (HCC) is the third most lethal malignancy worldwide, with a high incidence in China 1. Although liver transplantation and hepatic resection are the preferred treatment strategies for patients with HCC,2 image-guided percutaneous microwave ablation (PMWA) has been established as a frequent and acceptable therapeutic method for patients in the early stages of HCC, as defined by the Barcelona Clinic Liver Cancer staging system 3. This treatment technique has been associated with many theoretical advantages, such as higher intratumoral temperature, larger ablation volume, and less operation time, compared with radiofrequency ablation (RFA).…”
Section: Introductionmentioning
confidence: 99%